A review of 20 years (1999–2019) of Turkish–French collaboration in marine geoscience research in the Sea of Marmara - Géli, Louis; Henry, Pierre; Çağatay, M. Namik (Springer Science and Business Media LLC, 2021)
This paper retraces the history and main achievements of the ongoing Turkish–French collaboration in marine geoscience research in the Sea of Marmara, which was initiated in the aftermath of the 1999, Izmit and Duzce earthquakes. The collaboration resulted in nine large oceanographic cruises along with six recovery operations involving diverse vessels, and in the participation in two major EU-funded programmes (ESONET-NoE and MARSITE) and to one bilateral project, e.g. the MAREGAMI Project, co-funded by TUBITAK and ANR (the Turkish and French national funding agencies for research, respectively). In this paper, we review the major scientific contributions on the tectonic evolution of the North-Anatolian Fault in the Marmara Region; on the relationships between faulting, seismicity, fluids and ecosystems; and on paleo-seismology and paleo-oceanography in the Sea of Marmara.
Keywords: [SDU.STU.TE]Sciences of the Universe [physics]/Earth Sciences/Tectonics; [SDU.STU.TE] Sciences of the Universe [physics]/Earth Sciences/Tectonics; [SDU.STU] Sciences of the Universe [physics]/Earth Sciences; [SDU.STU]Sciences of the Universe [physics]/Earth Sciences; [SDU.STU.OC] Sciences of the Universe [physics]/Earth Sciences/Oceanography; [SDU.STU.OC]Sciences of the Universe [physics]/Earth Sciences/Oceanography